2021
DOI: 10.1155/2021/6634181
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dose Copper Exposure Exacerbates Depression‐Like Behavior in ApoE4 Transgenic Mice

Abstract: Depression is one of the most common neuropsychiatric disorders. Although the pathogenesis of depression is still unknown, environmental risk factors and genetics are implicated. Copper (Cu), a cofactor of multiple enzymes, is involved in regulating depression-related processes. Depressed patients carrying the apolipoprotein ε4 allele display more severe depressive symptoms, indicating that ApoE4 is closely associated with an increased risk of depression. The study explored the effect of low-dose Cu exposure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…On the other hand, copper may drive the activity of the two neurotrophic factors Brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) ( 28 ), which further influence the activity-dependent neural plasticity and neural network ( 29 ). Indeed, experimental evidence demonstrates that low-dose copper exacerbates depression-like behavior in ApoE4 transgenic mice ( 30 ). Differently from other metals, selenium incorporates into selenoproteins (glutathione per-oxidases and thioredoxin reductases) and protects from lipoperoxidation and oxidative cell damage (the glutathione antioxidant system is implicated in the pathophysiology of mood disorders) ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, copper may drive the activity of the two neurotrophic factors Brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) ( 28 ), which further influence the activity-dependent neural plasticity and neural network ( 29 ). Indeed, experimental evidence demonstrates that low-dose copper exacerbates depression-like behavior in ApoE4 transgenic mice ( 30 ). Differently from other metals, selenium incorporates into selenoproteins (glutathione per-oxidases and thioredoxin reductases) and protects from lipoperoxidation and oxidative cell damage (the glutathione antioxidant system is implicated in the pathophysiology of mood disorders) ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research on brain networks related to depression has also become one of the research hotspots in recent years. Some studies use specific tasks to stimulate depression patients and then compare the brain activity of normal controls [ 1 ]. It was found that the patient's prefrontal lobe, amygdala, hypothalamus, hippocampus, and other regions had abnormal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Copper might influence depression via inflammation, oxidative stress, or synaptic plasticity. Copper exposure increases depression-like behavior and activates inflammation-related microglia in APOE4 transgenic mice [ 116 ]. Melatonin (Mel) attenuates CU-induced oxidative stress and depression-like behavior by decreasing lipid peroxidation (LPO) and nitric oxide (NO) levels and enhancing superoxide dismutase (SOD) and catalase (CAT) activities in the rat hippocampus [ 117 ].…”
Section: Overdose or Deficiency Of Mineral Element Increase The Risk ...mentioning
confidence: 99%